2023
DOI: 10.1182/blood.2022018236
|View full text |Cite
|
Sign up to set email alerts
|

TP53mutation in therapy-related myeloid neoplasm defines a distinct molecular subtype

Abstract: Key Points Not applicable Not applicable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…Consistent with our previous observation [ 20 ], the OS was not significantly different between the single- and multi-hit TP53 mut t-MN (Fig. 2J ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our previous observation [ 20 ], the OS was not significantly different between the single- and multi-hit TP53 mut t-MN (Fig. 2J ).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, in MDS and AML with CK, the single- or multi-hit TP53 mut was the only disease-related factor predicting survival [ 14 ]. We recently demonstrated that TP53 mut t-MN is associated with poor survival irrespective of single or multi-hit status [ 20 ], suggesting that the prognostic impact of allelic loss of TP53 mut MN is context dependent.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism for the relative preponderence of TP53 mutations in MDS‐del(5q), which by definition requires the absence of complex karyotype, remains obscure; the possibility of a contributory role from therapy‐related disease is suggested, in the current study, by the non‐significantly higher frequency of TP53 mutation in therapy‐related disease (30% vs. 19%), as was the case for TP53 VAF ≥22% (Table 1). In the latter scenario regard, we have previously shown that TP53 mutation with ≥10% VAF was prognostically detrimental in therapy‐related myeloid neoplasms, regardless of allelic state or BM blast count 16 ; in the particular study, TP53 mutation frequency was 37.3% in patients with <5% BM blast percentage vs. 38.1%–38.2% in those with 5%–19% blast percentage; furthermore, overall survival was similar between different blast categories of MDS harbouring <20% BM blast percentage.…”
Section: Discussionmentioning
confidence: 97%
“…Concerning general characteristics and genetic features of t‐AML patients, as others, we reported more frequent abnormal karyotypes compared to de novo AML 2,15,17,18,45,46 and no difference in the incidence and distribution of mutated NPM1 and FLT3‐ITD between t‐AML and de novo AML 47 . TP53 mutations or 17p abnormalities are frequently observed in t‐MNs and associated with complex karyotype, a reduced probability of achieving response after induction chemotherapy and a poor outcome, as shown by Lindsley et al 48 Nowadays, prognosis of TP53 mutated t‐AML, according to new AML classifications 26 must consider variant allelic frequency, single or multihit characteristic and presence of comutations 49 . Due to NGS nonavailability at the beginning of our study, we reported only few results of genomic assessment in 13 patients with 2 or more mutations and TP53 mutations in 46% co‐occurring, in half of them with chromosome 17 abnormalities.…”
Section: Discussionmentioning
confidence: 99%